Zhili decoction ameliorates ulcerative colitis by modulating gut microbiota and related metabolite, and inhibiting the TLR4/NF-κB/NLRP3 pathway - Tan, Tianying; Chen, Qin; Chen, Ping; Li, Shuangshuang; Hu, Wenting; Yang, Tao; Jia, Yingtian (Frontiers in Pharmacology, 2024)
Ethnopharmacological ImportanceZhili decoction (ZLD) is a traditional Chinese medicine prescription for ulcerative colitis (UC). However, the mechanism by which ZLD exerts its therapeutic effects in the context of UC remains unclear.Aim of studyThe aim of this study was to investigate the effects of ZLD on the gut microbiota and related fecal metabolite levels using a mouse model of UC. In addition, we examined the underlying molecular mechanisms responsible for these effects.Materials and methodsThe major components of ZLD were detected by ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). An integrated approach employing 16S rRNA and fecal metabolomics was employed to assess the potential impacts of ZLD on gut flora abundance and diversity, fecal metabolite levels, and various metabolic pathways. To further investigate the potential mechanisms of ZLD in treating UC, the expression of genes and proteins were examined by RT-qPCR, immunohistochemical staining and Western blotting.ResultsZLD markedly alleviated symptoms and inflammatory injury in mice with UC. DSS induced notable alterations in the gut microbiome, and ZLD enhanced gut microbial diversity in UC mice by augmenting the abundance of Bacteroidota, Christensenella, Lactobacillus, etc., while reducing the Firmicutes/Bacteroidota ratio. ZLD treatment significantly modified the metabolic profile of mice with UC. It significantly suppressed the arachidonic acid metabolic pathway and promoted the butyrate acid metabolic pathway. ZLD reduced inflammatory factors and inhibited TLR4/NF-κB/NLRP3 pathway expression. In addition, correlation analysis demonstrated a close relationship between gut microbes, fecal metabolites, and inflammatory factors.ConclusionZLD alleviated UC by regulating gut flora, modulating related metabolite levels, and inhibiting TLR4/NF-κB/NLRP3 pathway.